Population genomic analysis of clinical ST15 Klebsiella pneumoniae strains in China - Feng, Li; Zhang, Mingcheng; Fan, Zhiyi (Frontiers in Microbiology, 2023)
ST15 Klebsiella pneumoniae (Kpn) is a growing public health concern in China and worldwide, yet its genomic and evolutionary dynamics in this region remain poorly understood. This study comprehensively elucidates the population genomics of ST15 Kpn in China by analyzing 287 publicly available genomes. The proportion of the genomes increased sharply from 2012 to 2021, and 92.3% of them were collected from the Yangtze River Delta (YRD) region of eastern China. Carbapenemase genes, including OXA-232, KPC-2, and NDM, were detected in 91.6% of the studied genomes, and 69.2% of which were multidrug resistant (MDR) and hypervirulent (hv). Phylogenetic analysis revealed four clades, C1 (KL112, 59.2%), C2 (mainly KL19, 30.7%), C3 (KL48, 0.7%) and C4 (KL24, 9.4%). C1 appeared in 2007 and was OXA-232-producing and hv; C2 and C4 appeared between 2005 and 2007, and both were KPC-2-producing but with different levels of virulence. Transmission clustering detected 86.1% (n=247) of the enrolled strains were grouped into 55 clusters (2–159 strains) and C1 was more transmissible than others. Plasmid profiling revealed 88 plasmid clusters (PCs) that were highly heterogeneous both between and within clades. 60.2% (n=53) of the PCs carrying AMR genes and 7 of which also harbored VFs. KPC-2, NDM and OXA-232 were distributed across 14, 4 and 1 PCs, respectively. The MDR-hv strains all carried one of two homologous PCs encoding iucABCD and rmpA2 genes. Pangenome analysis revealed two major coinciding accessory components predominantly located on plasmids. One component, associated with KPC-2, encompassed 15 additional AMR genes, while the other, linked to OXA-232, involved seven more AMR genes. This study provides essential insights into the genomic evolution of the high-risk ST15 CP-Kpn strains in China and warrants rigorous monitoring.